Identification of bioactive anti-angiogenic components targeting tumor endothelial cells in Shenmai injection using multidimensional pharmacokinetics - Chongjin Zhong; Chao Jiang; Suiying Ni; Qizhi Wang; Lingge Cheng; Huan Wang; Qixiang Zhang; Wenyue Liu; Jingwei Zhang; Jiali Liu; Mulan Wang; Min Jin; et al. (Elsevier, 2020)
Shenmai injection (SMI) is a well-defined herbal preparation that is widely and clinically used as an adjuvant therapy for cancer. Previously, we found that SMI synergistically enhanced the activity of chemotherapy on colorectal cancer by promoting the distribution of drugs in xenograft tumors. However, the underlying mechanisms and bioactive constituents remained unknown. In the present work, the regulatory effects of SMI on tumor vasculature were determined, and the potential anti-angiogenic components targeting tumor endothelial cells (TECs) were identified. Multidimensional pharmacokinetic profiles of ginsenosides in plasma, subcutaneous tumors, and TECs were investigated. The results showed that the concentrations of protopanaxadiol-type (PPD) ginsenosides (Rb1, Rb2/Rb3, Rc, and Rd) in both plasma and tumors, were higher than those of protopanaxatriol-type (Rg1 and Re) and oleanane-type (Ro) ginsenosides. Among PPD-type ginsenosides, Rd exhibited the greatest concentrations in tumors and TECs after repeated injection. In vivo bioactivity results showed that Rd suppressed neovascularization in tumors, normalized the structure of tumor vessels, and improved the anti-tumor effect of 5-fluorouracil (5FU) in xenograft mice. Furthermore, Rd inhibited the migration and tube formation capacity of endothelial cells in vitro. In conclusion, Rd may be an important active form to exert the anti-angiogenic effect on tumor after SMI treatment.